The Data Librarian's Handbook - Longo, Brunella (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
A well rounded disenchanted and yet optimistic book review in a subject increasingly pivotal for the future of our profession: should data librarianship be confined, as the authors of this handbook suggest, to the academic library? and what is, in the end, that qualifies librarianship's theory and practice to deal with data and research data in particular?